2018
DOI: 10.5858/arpa.2017-0054-oa
|View full text |Cite
|
Sign up to set email alerts
|

Use of the National Institutes of Health Consensus Guidelines Improves the Diagnostic Sensitivity of Gastrointestinal Graft-Versus-Host Disease

Abstract: - Use of the NIH histology consensus guidelines results in a high sensitivity and specificity, thereby decreasing false-negatives. Additionally, use of the NIH guidelines aids in creating uniformity and diagnostic clarity. Correlation with clinical and laboratory findings is critical in evaluating the differential diagnosis and to avoid false-positives. As expected, increased apoptosis with decreased inflammation was associated with a pathologic diagnosis of graft-versus-host disease and supports the NIH guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…12,17,18 Furthermore, we used the GI-GVHD histological In a previous adult patient study, with a design similar to our study, 64% of the endoscopies with histopathology-based non-GI-GVHD diagnosis in CSHA were reclassified as GI-GVHD in a re-evaluation. 37 The corresponding result in our study was 48%.…”
supporting
confidence: 65%
“…12,17,18 Furthermore, we used the GI-GVHD histological In a previous adult patient study, with a design similar to our study, 64% of the endoscopies with histopathology-based non-GI-GVHD diagnosis in CSHA were reclassified as GI-GVHD in a re-evaluation. 37 The corresponding result in our study was 48%.…”
supporting
confidence: 65%
“…The normal number of crypt apoptotic bodies in small intestinal mucosa is controversial, though for the purposes of graft-versus-host-disease diagnosis, the National Institutes of Health consensus statements suggests 1 per biopsy fragment [14]. This value is highly sensitive, though not specific for graft-versus-host disease [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this confusion about the threshold, excessive crypt apoptosis is abnormal and is associated with certain disease states, such as graft-versus-host disease, acute cellular rejection in small bowel allografts, and medication injury, such as in patients with toxicity due to mycophenolate mofetil [16, 17]. Apoptosis in intestinal crypts has been demonstrated in biopsies of active celiac disease by a variety of methods, including nick-end labelling assays [15, 17] and immunohistochemistry for epithelial apoptosis markers [1820]. Studies have shown an increase in the degradation end products of apoptosis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…H&E slides were examined for apoptoses in the surface epithelium and deep crypts/glands. Deep crypt/gland apoptosis was considered increased when there was ≥2 intraepithelial apoptoses per tissue fragment based on the National Institutes of Health consortium guidelines for the histologic diagnosis of GI graft‐versus‐host disease 2,3 . In PrEP patients, the highest apoptotic body count in the surface epithelium and in the deep crypts/glands per tissue fragment was recorded for each biopsy site.…”
Section: Methodsmentioning
confidence: 99%